Design-build of photovoltaic panel data logger pressure - Masarrang, Maryantho; Dewi, Sari; Mustari, Aidynal; Arifin, Yusnaini; Fauzi, Rizana (Prodi Teknik Informatika FIK Universitas Muslim Indonesia, 2021)
The scarcity of fossil fuel sources and the growing energy demand has resulted in more intensively searching for alternative energy. One alternative energy source that is suitable for the equatorial region is solar energy. One of the technologies for utilizing solar energy that has begun to be widely used in Indonesia is the photovoltaic (PV) system. The output of PV is highly dependent on environmental conditions, especially the intensity of the sun and temperature. In addition to these two factors, shading (shadows) and soiling (dust) also affects the PV output. So, this must be observed at all times by monitoring the voltage and current as the PV output. This study aims to design a PV panel instrumentation structure based on a data logger. PV output data in the form of voltage and current and environmental conditions such as ambient temperature and solar intensity were recorded in real-time. The measurement results from the data logger will be compared with manual measurements. PV output data, output voltage and current, as well as sunlight intensity were compared with measurements using an avometer. Temperature data will be compared with thermocouple measurements. PV in this study will be connected to a 1kOhm load resistor. The results of the data logger and manual measurements indicated an insignificant difference. The manual measurement was conducted every hour, from 09.00 16.00. The maximum differences for voltage, PV output current, pyranometer voltage, and ambient temperature are 0.89 V, 0.0007 A, 0.00014 V, and 0.25oC, respectively.